Biopsychosocial factors in oral and systemic diseases: a scoping review - Hensel, Abby L. J.; Nicholson, Kathryn; Anderson, Kelly K.; Gomaa, Noha A. (Frontiers in Oral Health, 2024)
The association between chronic oral diseases and other major systemic health conditions, commonly referred to as the oral-systemic health connection, has been previously studied with several underlying common risk factors and pathways linking both groups of diseases. Psychosocial factors contribute to an increased susceptibility to chronic oral and non-oral diseases. The aim of this review is to summarize the current state of knowledge on the role of psychosocial stress in chronic oral and systemic diseases.Methods: A search strategy was built and a literature search was conducted using four databases (CINAHL, Embase, Medline, PsycINFO). A combination of search terms related to psychosocial stress, systemic disease, and oral conditions were used. Studies were eligible for inclusion if they included human adults (aged 18 years and older), included psychosocial factors as an exposure measure, and outcome measures of both an oral and systemic condition. Only English-language articles were considered. Pilot testing of the data extraction form and calibration were conducted and data were extracted independently by one researcher.Results: A total of fifteen articles out of eighty full-text articles screened were determined to be eligible for inclusion in this review. Periodontal disease was the most commonly studied oral disease, measured in 53% of included articles, with the most commonly studied systemic diseases being of mental health conditions (40%) and diabetes (47%). Psychosocial stress was measured using a range of psychometric indicators and/or biomarkers, including perceived stress, individual behaviours, childhood adversity, and cortisol. In total, fourteen studies found a positive association between measures of psychosocial stress and oral-systemic health.Psychosocial stress may be a common contributor to both chronic oral and non-oral diseases.